Utilização do geogebra como ferramenta para o ensino de trigonometria - Costa, Andressa Solane Moreira (2017)
The main objective of this work is to contribute in the academic scope for the teaching of Trigonometry. In this way, the present work is based on an action research that takes as a base the use of technological resources in the teaching of mathematics with focus in Trigonometry. Thus, it will be presented the use of dynamic geometry environments for teaching mathematics, especially the use of GeoGebra software, as well as the theoretical basis of Trigonometry, as well as a proposal and application of Trigonometry teaching using GeoGebra.